The Cognitive Functioning of Socially Isolated Individuals may Profit from High Mental Work Demands - Then, F. S.; Schroeter, M. L.; Witte, V.; Engel, Christoph; Löffler, Markus; Thiery, J.; Villringer, A.; Luck, Tobias; Riedel-Heller, Steffi Gerlinde (Das Gesundheitswesen, 2016)
Objectives: Previous studies have shown that individuals with poor social relationships have an increased risk for dementia. Dementia risk, however, can also be positively influenced by lifestyle factors. One such very important factor is high mental demands at work, in particular as the work environment affects a very long lifetime period. Thus, our objective was to investigate whether the cognitive functioning of socially isolated individuals may profit from high mental work demands.